Glucosamine Supplementation Demonstrates a Negative Effect On Intervertebral Disc Matrix in an Animal Model of Disc Degeneration - Jacobs, Lloydine (2013)
STUDY DESIGN: Laboratory based controlled in vivo study OBJECTIVE: To determine the in vivo effects of oral glucosamine sulfate on intervertebral disc degeneration SUMMARY OF BACKGROUND DATA: Although glucosamine has demonstrated beneficial effect in articular cartilage, clinical benefit is uncertain. A CDC report from 2009 reported that many patients are using glucosamine supplementation for low back pain (LBP), without significant evidence to support its use. Because disc degeneration is a major contributor of LBP, we explored the effects of glucosamine on disc matrix homeostasis in an animal model of disc degeneration. METHODS: Eighteen skeletally mature New Zealand White rabbits were divided into four groups: control, annular puncture, glucosamine, and annular puncture+glucosamine. Glucosamine treated rabbits received daily oral supplementation with 107mg/day (weight based equivalent to human 1500mg/day). Annular puncture surgery involved puncturing the annulus fibrosus (AF) of 3 lumbar discs with a 16G needle to induce degeneration. Serial MRIs were obtained at 0, 4, 8, 12, and 20 weeks. Discs were harvested at 20 weeks for determination of glycosaminoglycan(GAG) content, relative gene expression measured by RT-PCR, and histological analyses. RESULTS: The MRI index and NP area of injured discs of glucosamine treated animals with annular puncture was found to be lower than that of degenerated discs from rabbits not supplemented with glucosamine. Consistent with this, decreased glycosaminoglycan was demonstrated in glucosamine fed animals, as determined by both histological and GAG content. Gene expression was consistent with a detrimental effect on matrix. CONCLUSIONS: These data demonstrate that the net effect on matrix in an animal model in vivo, as measured by gene expression, MRI, histology, and total proteoglycan is anti-anabolic. This raises concern over this commonly used supplement, and future research is needed to establish the clinical relevance of these findings.